THE UTILIZATION OF 4 PICS 1 WORD APPLICATION IN LEARNING ENGLISH VOCABULARY : EXPLORING EFL STUDENTS’ PERSPECTIVE - Matondang, Rahmah; Purnomo, Maslathif Dwi; Berutu, Hotma (TELL - US JOURNAL, 2024)
There has been many technological tools utilized to support human activities, particularly in education. This study aimed to investigate the EFL students’ perception on 4 Pics 1 Word application in learning English vocabulary. The study used qualitative design as the research methodology. The participants of this study were 20 Indonesian Senior High School students who chose purposively based on their experience in using 4 Pics 1 Word app. Questionnaire and semi-structured interview were employed as the research instrument for this study. The questionnaire focused on the students’ perception on utilizing 4 Pics 1 Word app, while the semi-structured interview questions were focused on the effects of utilizing 4 Pic 1 Word app in students’ vocabulary skills. This study came up with the findings that the majority of participants gave positive response on 4 Pics 1 Word app as gamified learning in improving vocabulary mastery. The utilization of 4 Pics 1 Word app gives positive effects to the students on various things such as more motivated in collecting new words, increased confidence in expressing oneself, improved analysation skills and improved reading comprehension skills.